Kakila database of marine mammal observation data around the French archipelago of Guadeloupe in the AGOA sanctuary - French Antilles - Lorraine Coché; Elie Arnaud; Bouveret Laurent; Romain David; Eric Foulquier; Nadège Gandilhon; Etienne Jeannesson; Yvan Le Bras; Emilie Le Rigoleur; Pascal Jean Lopez; Bénédicte Madon; Julien Sananikone; et al. (PNDB Metacat Node, 2021)
Database collected as part of the Lorraine Coché master's 2 internship "Inventory and structuring of marine mammal observation data around Guadeloupe" in 2020 (Master Tropical marine ecosystems at the University of the Antilles). This database centralizes and harmonizes the data collected by the team of the Agoa Sanctuary (Aire Marine Protégée), the OMMAG (Observatory of Marine Mammals of the Guadeloupe Archipelago), the NPO BREACH, and whale-watching companies Cétacés Caraïbes, Guadeloupe Evasion Découverte et Aventures Marines.